2015
DOI: 10.1056/nejmoa1411817
|View full text |Cite
|
Sign up to set email alerts
|

AZD9291 in EGFR Inhibitor–Resistant Non–Small-Cell Lung Cancer

Abstract: AZD9291 was highly active in patients with lung cancer with the EGFR T790M mutation who had had disease progression during prior therapy with EGFR tyrosine kinase inhibitors. (Funded by AstraZeneca; ClinicalTrials.gov number, NCT01802632.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
1,494
5
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 1,853 publications
(1,566 citation statements)
references
References 26 publications
46
1,494
5
21
Order By: Relevance
“…220,221,236 Data are emerging 237 that a second acquired resistance mutation, C797S, can arise in tumors that have progressed after osimertinib treatment for T790M disease, but these cases are so far rare and this mutation is poorly studied and not currently treatable, so testing for C797S is not recommended for routine management at this time.…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…220,221,236 Data are emerging 237 that a second acquired resistance mutation, C797S, can arise in tumors that have progressed after osimertinib treatment for T790M disease, but these cases are so far rare and this mutation is poorly studied and not currently treatable, so testing for C797S is not recommended for routine management at this time.…”
Section: Recommendationmentioning
confidence: 99%
“…Such testing is particularly appropriate because third-generation EGFR inhibitors (eg, osimertinib) are proven to have significant benefit for T790M mutant cancers 221 and have been approved for this indication by health authorities around the world. Analysis of cfDNA or analysis of a new tissue biopsy is appropriate for EGFR T790M detection.…”
Section: Expert Consensus Opinionmentioning
confidence: 99%
“…As regards the other new-generation TKIs, unfortunately the clinical development of both rociletinib and olmutinib has been recently stopped, even if both these agents had already received the FDA-break-through therapy designation in lung cancer. Despite the promising activity observed in phase I study (Jänne et al, 2015), the updated "confirmed" response rate to rociletinib dropped from 59% to 39% at 625 mg bid dose (n = 175) and to 25% at 500 mg bid dose (n = 156) in T790M-positive patients (Sequist et al, 2015;Goldman et al, 2016). These data, along with the high rate of G3-4 hyperglycemia and QTc prolongation reported in TIGERX trial, led to the FDA notification with the subsequent stopping of patients' enrollment in all ongoing trials with rociletinib.…”
Section: New Generation Egfr-tkismentioning
confidence: 92%
“…The understanding of the molecular pathology of tumours in unprecedented detail coupled with modern drugs and associated diagnostic technologies to select patients has enabled tangible improvements in survival rates in some cancer types 10-17 ; particularly exemplified in patients with Non Small Cell Lung Cancer (NSCLC) 13,16 . More recently, significant durable responses to immune modulatory therapies are emerging in ~15% of patients.…”
Section: Principles and Evolution Of Clinical Trialsmentioning
confidence: 99%
“…Such advances have ushered in a new era of therapeutics that target specific molecular processes. Although we have had some dramatic successes [8][9][10][11][12][13][14][15][16][17] , the overall strategy remains in its infancy 18 . The central premise of precision medicine is that by matching a drug and its mechanism of action to select patients we can offer greater potential for durable clinical benefit -often referred to as "matching the right drug to the right patient".…”
Section: Introductionmentioning
confidence: 99%